Quenched hexacene optoacoustic nanoparticles - Nunes, Antonio; Pansare, Vikram J.; Beziere, Nicolas; Ntoukas, Argiris Kolokithas; Reber, Josefine; Bruzek, Matthew; Anthony, John; Prud'Homme, Robert K.; Ntziachristos, Vasilis (Journal of Materials Chemistry B, 2017)
Optoacoustic (photoacoustic) imaging enables high-resolution optical imaging at depths well beyond optical microscopy, revolutionizing optical interrogation of tissues. Operation in the near-infrared (NIR) is nevertheless necessary to capitalize on the technology potential and reach depths of several centimeters. Using Flash NanoPrecipitation for highly-scalable single-step encapsulation of hydrophobic hexacene at self-quenching concentrations, we propose quenched fluorescence-dye nanoparticles as a potent alternative to NIR metal nanoparticles for strong optoacoustic signal generation. Comprehensive hexacene-based nanoparticle characterization was based on a 5-step approach that examined the physicochemical features (Step 1), optoacoustic signal generation (Step 2), stability (Step 3), biocompatibility (Step 4) and spectral sensitivity (Step 5). Using this characterization framework we showcase the discovery of two nanoparticle formulations, QH2-50 nm and QH2-100 nm that attain superior stability characteristics and optimal optoacoustic properties compared to gold standards commonly employed for near-infrared optoacoustics. We discuss encapsulation and self-quenching (ESQ) of organic dyes as a promising strategy to generate optimal optoacoustic particles.
CRIS-Team Scopus Importer:2023-03-08